PENGARUH PEMBERIAN DOSIS PUPUK NPK PAK TANI DAN PUPUK ORGANIK SUPERNASA GRANUL TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN GAMBAS (Luffa acutangula L.) VARIETAS SENOPATI - Abu Talkah; Wahyu Widya Larasati; Samudi . (Universitas Islam Kadiri, 2017)
The efforts to increase the production of Luffa acutangulais provide fertilizer that plants needed. Fertilization is an important factor in the growth and cultivation of plants. Fertilization that is not in not in accordance with needs of plants can involve plants to deficiency or excess so growth plants is not optimal. Therefore, the requiredof exactly dose and not maximum results. The purpose of this research is to know the interaction between dose of NPK “Pak Tani” fertilizer and dose of “Supernasa Granule” fertilizer to growth and production of Luffaacutangula L. varieties “Senopati”. This research was conducted in Wates Village, Kec. Campurdarat, Tulungagung District. This research was conducted from February to May 2017. The result of this research is no interaction of dose of NPK “Pak Tani” fertilizer and “Supernasa Granule” fertilizer to all observation variables